Metakognisi Dosen dalam Proses Pembelajaran: Kajian Kualitatif di IKIP Nusantara - M. Djauzi Mudzakir (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1999)
This research aimed at understanding and explaining the metacognition that the lecturers experienced in their teaching. The subjects of this case study were 9 lecturers of IKIP Nusantara; the case was the metacognition of the nine lecturers, and the analysis units were their respective lectures. The data were comprised of the lecturers’ teaching acts, the process of their metacognition and their personal perception and philosophy in the forms of verbal self-reports obtained from interview. The findings show that the quality of instruction depends on the quality of the lecturers’ metacognition. Therefore, the realization of the comprehensive goals of education in the process of learning and teaching lies on the willingness and seriousness of the lecturers to monitor and tailor their teaching and learning according to the true concept of education.